Efektivitas Penggunaan Aplikasi Srikandi dan Kualitas SDM dalam Meningkatkan Produktivitas Pegawai di Arsip Nasional Republik Indonesia - Rahmawati, Dwitya Nur; Winata, Hendri; Febrianto, Abi Sopyan (Universitas Pendidikan Indonesia, 2024)
Various impacts of current globalization require organizations to continue to develop in accordance with predetermined goals and policies. Problems that still often arise in an agency are the inadequate employee performance, the inadequate use of technology, and the low quality of human resources. In its development, the agency has improved employee performance through several strategies and programs that support the implementation of work. This analysis aims to determine employee views on the SRIKANDI application, the influence of human resource quality and employee performance level assessments at ANRI. This study uses a quantitative method by collecting data through distributing questionnaires to 93 ANRI employees and the data is analyzed using descriptive and inferential data. Based on the results of this study, the SRIKANDI Application is in the fairly effective category, the quality of human resources and employee performance are in the moderate category. The results of hypothesis testing indicate the influence of the SRKANDI Application and the quality of human resources on employee performance. And when viewed from the value of the influence of the SRIKANDI Application and the quality of human resources, it has a fairly strong influence on employee performance.